2009
DOI: 10.1111/j.1467-8535.2009.00941.x
|View full text |Cite
|
Sign up to set email alerts
|

Learning in 3‐D multiuser virtual environments: Exploring the use of unique 3‐D attributes for online problem‐based learning

Abstract: The purpose of this article is to present the results of a study conducted to investigate how the attributes of 3-D technology such as avatars, 3-D space, and comic style bubble dialogue boxes affect participants' social, cognitive, and teaching presences in a blended problem-based learning environment. The community of inquiry model was adopted to analyse and interpret data collected from transcripts and group interviews. The results indicated that although the attributes of 3-D technology promoted participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(49 citation statements)
references
References 14 publications
(16 reference statements)
3
40
0
2
Order By: Relevance
“…One of the most widely used 3D environments in educational settings is Second Life (SL), mainly due to its abilities of building rich 3-D environments, highly immersive for players with a relatively low cost to participate [20]. In brief, studies showed that 3-D worlds offered a fun and engaging approach towards learning, while the involvement of professionals and the context of future tasks in a realistic setting increased their motivation [21].…”
Section: Use Of Technology In Pblmentioning
confidence: 99%
“…One of the most widely used 3D environments in educational settings is Second Life (SL), mainly due to its abilities of building rich 3-D environments, highly immersive for players with a relatively low cost to participate [20]. In brief, studies showed that 3-D worlds offered a fun and engaging approach towards learning, while the involvement of professionals and the context of future tasks in a realistic setting increased their motivation [21].…”
Section: Use Of Technology In Pblmentioning
confidence: 99%
“…A virtual gallery will enhance traditional pedagogical methods by ensuring viewing is active and no longer passive. According to Omale et al, the development of 3-D virtual elements is an exciting trend with the potential to enable global cultural diffusion (Omale et al, 2009). Ulusoy's study aimed to determine whether the attitudes of open education students would be changed by the implementation of a virtual museum application.…”
Section: Application Areasmentioning
confidence: 99%
“…The studies comparing traditional classroom environment with virtual one (Edirisingha, Nie, Pluciennik, & Young, 2009;Omale, Hung, Luetkehans, & Cooke-Plagwitz, 2009;Salmon, 2009;Warburton, 2009) suggest that the feeling of existence and belonging in the virtual environment is higher than that of the traditional classroom environment. Simultaneous communication in the virtual environment has a motivating effect on students (Holmberg & Huvila, 2008;Omale et al, 2009). According to Arıcı (2013), the academic achievement of students studying in the virtual world is higher than in traditional classrooms, and the information gained is more permanent.…”
Section: Introductionmentioning
confidence: 99%